Inter-format competition among retailers: The role of private label products in market delineation - Justus Haucap; Ulrich Heimeshoff; Gordon J. Klein; Dennis Rickert; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper analyses the extent of inter-format retail competition between supermarkets, discounters and drugstores in Germany, using data from the German market for diapers. We estimate a random coefficient logit model at the individual household level. Based on consumer substitution patterns, we calculate manufacturers' and retailers' estimated marginal costs and margins and, based on these margins, apply standard market delineation techniques which suggest that the strongest substitution patterns are between the leading manufacturer brand and private labels sold at drugstores and discounters. This finding contrasts with recent speculations by competition authorities that private label products may belong to a different antitrust market than manufacturers' brands.
Keywords: L1; L4; L8; C5; 330; Discrete Choice; Demand Estimation; Market Delineation; Grocery Retail Markets; Antitrust